(untitled) (Progressive Agriculture, 2013)
This study was conducted to identify the technical and economical performance of the existing models of maize sheller in the country and suggest the best maize sheller models for the farmers during 3 September 2006 to 30 March 2007 in the area of Bogra, Rangpur, Dinajpur, Rajshahi and Jessore. Detail field tests were conducted on seven selected maize sheller models of three categories to assess the comparative performance. Three basic designs of maize sheller models were identified through field survey and secondary information. The models were Spike-pinion (SP) type, Spiral rasp-bar cylinder (SBC) type and Parallel rasp-bar cylinder (PBC) type. The technical performances of the selected maize sheller models were evaluated on the basis of throughput capacity, shelling capacity, cylinder loss, separating loss, broken kernel and shelling efficiency. The shelling capacity and efficiency of Binimoy and Sarker spike-pinion (SP) type models were found about 0.45 ton/hr and 93%, respectively. Similarly, the shelling capacities and efficiencies of Farida, Rahman and Uttaran spiral rasp-bar cylinder (SBC) models were ranged between 2.8 to 4.0 ton/hr and 93 to 97%, respectively. Farida parallel rasp-bar (PBC) type maize sheller had shown incredible shelling efficiency of about 99% with almost negligible cylinder (0.25%) and separating (0.25%) losses along with lowest broken kernel (2.5%) percentage. However, the shelling capacity was found comparatively low about 1.9 ton/hr. The shelling costs, benefit-cost ratios and net margins of spiral rasp-bar cylinder models vary between Tk. 91-97/ton, 1.28-1.37 and Tk78-134/hr, respectively. Among the models Farida (SBC) appeared as the most economic one having lowest shelling cost of Tk. 91/ton with the highest benefit-cost ratio of 1.37 and net margin of Tk. 134/hr (determined at a custom-hire rate of Tk. 7 per 40 kg of shelled kernel). Comparative economic uses of the selected maize shellers suggest that the use of hand sheller is beneficial up to an annual use of 13 ton. Whereas, Binimoy (SP) and Sarker (SP) models are economic for annual use between 13 and 30 ton, and Farida (SBC), Rahman (SBC) and Uttaran (SBC) models are economic for shelling over 30 ton per annum. Economic analysis suggest that hand sheller could be beneficial for very small farm holdings, Binimoy (SP) and Sarker (SP) models for small farm holdings and Farida (SBC), Rahman (SBC) and Uttaran (SBC) models for medium to large farm holdings and custom-hire service. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16873 Progress. Agric. 20(1 & 2): 207 220, 2009